Effects of Nitric Oxide on Voltage-Gated K+ Currents in Human Cardiac Fibroblasts through the Protein Kinase G and Protein Kinase A Pathways but Not through S-Nitrosylation - Hyemi Bae (International Journal of Molecular Sciences, 2018)
This study investigated the expression of voltage-gated K+ (KV) channels in human cardiac fibroblasts (HCFs), and the effect of nitric oxide (NO) on the KV currents, and the underlying phosphorylation mechanisms. In reverse transcription polymerase chain reaction, two types of KV channels were detected in HCFs: delayed rectifier K+ channel and transient outward K+ channel. In whole-cell patch-clamp technique, delayed rectifier K+ current (IK) exhibited fast activation and slow inactivation, while transient outward K+ current (Ito) showed fast activation and inactivation kinetics. Both currents were blocked by 4-aminopyridine. An NO donor, S-nitroso-N-acetylpenicillamine (SNAP), increased the amplitude of IK in a concentration-dependent manner with an EC50 value of 26.4 µM, but did not affect Ito. The stimulating effect of SNAP on IK was blocked by pretreatment with 1H-(1,2,4)oxadiazolo[4,3-a]quinoxalin-1-one (ODQ) or by KT5823. 8-bromo-cyclic GMP stimulated the IK. The stimulating effect of SNAP on IK was also blocked by pretreatment with KT5720 or by SQ22536. Forskolin and 8-bromo-cyclic AMP each stimulated IK. On the other hand, the stimulating effect of SNAP on IK was not blocked by pretreatment of N-ethylmaleimide or by DL-dithiothreitol. Our data suggest that NO enhances IK, but not Ito, among KV currents of HCFs, and the stimulating effect of NO on IK is through the PKG and PKA pathways, not through S-nitrosylation.